Stock, composition and distribution of the nursing workforce in Brazil: a snapshot - Ana Paula Cavalcante de Oliveira; Ana Beatriz Zanardo Mion; Mariana Lopes Galante; Gabriela Di Donato; Carla Aparecida Arena Ventura (Universidade de São Paulo, 2024)
Abstract Objective: to analyze the availability (in terms of stock and composition) and accessibility (in terms of geographical distribution) of the nursing workforce in Brazil. Method: this is a descriptive, cross-sectional study with retrospective data collection, identified by combining databases available on institutional websites and structured according to indicators from the World Health Organization's "National Health Workforce Accounts". The study considered nursing professionals at senior level (nurses) and middle level (nursing auxiliaries and technicians). Indicators of stock, composition, distribution (by age group and gender) and the ratio of nurses to doctors were included. Results: there was an increase in the number of personnel between 2005 and 2010, mainly in middle and technical level professionals. There are more personnel aged between 36 and 55, with a predominance of women in all categories, despite the increase in men. There was an uneven distribution of personnel across the country's regions, with the Southeast having the largest number of professionals. The ratio of nurses to doctors is less than one in the South and Southeast. Conclusion: despite the large number of nurses, their distribution is uneven. The growth of nursing technicians has significantly outstripped that of nurses, indicating more intensive technical training policies than those found in higher education.